Ordered structures of dichain cationic surfactants at interfaces - McGillivray, D; Thomas, R; Rennie, A; Penfold, J; Sivia, D (2003)
We have observed stable layered structures adsorbed at the silicon-water and air-water interfaces from N,N-didodecyl-N,N-dimethylammonium bromide surfactant (DDAB) and the corresponding diundecyl compound (DUDAB). The structures were studied by neutron reflection at the wet hydrophilic silicon interface, and at the air-water interface, at concentrations of 0.2-2% w/w. The structures formed are found to have a high sensitivity to temperature, with the repeat spacing decreasing approximately reversibly by about 50% with an increase of temperature of about 40°C. Associated with the specular scattering there is pronounced off-specular scattering, indicative of a degree of lateral structure or dynamic fluctuation. The observations are consistent with two to four correlated layers which could arise from adsorbed monodisperse unilamellar vesicles, a lamellar phase, or a structured bicontinuous phase. Studies of the bulk solutions with X-ray scattering and cryo transmission electron microscopy show only coexisting unilamellar vesicles and lamellar phase.